Radical chemistry of 8-oxo-7,8-dihydro-2'-deoxyadenosine and 8-oxo-7,8-dihydro-2'-deoxyguanosine: a pulse radiolysis study. - Singh, T; Rao, B; O'Neill, P (2010)
The reactions of oxidizing ((•)OH, N(3)(•), and SO(4)(•-)) and reducing (e(aq)(-)) radicals with 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxoG) and 8-oxo-7,8-dihydro-2'-deoxyadenosine (8-oxoA) have been studied by pulse radiolysis to elucidate the initial free radical processes in their oxidation since these oxidized purines are readily oxidized in DNA. The second-order rate constants for the reaction of the (•)OH with 8-oxoA and 8-oxoG were determined to be 4.3 × 10(9) and 4.8 × 10(9) dm(3) mol(-1) s(-1), respectively. Similar values were also obtained with the N(3)(•) radical, the respective values being 8.8 × 10(9) and 3.8 × 10(9) dm(3) mol(-1) s(-1). The transient absorption spectrum following reaction of 8-oxoA with (•)OH is assigned to the C4- and C5-OH adducts which then undergo dehydration (k = 5.1 × 10(3) s(-1)) to give a reducing neutral N-centered radical. 8-oxoG, on the other hand, either reacts by H abstraction from the amino group attached to C2, which undergoes fast tautomerization or the resulting (•)OH adduct which rapidly dehydrates (k > 1.7 × 10(6) s(-1)) to give the species corresponding to the one-electron oxidized product. The transient absorption spectrum measured for the reaction of the N(3)(•) with 8-oxoG is identical to that obtained with the (•)OH at pH 10. The rate determining step is the formation of the radical cation which then rapidly loses a proton to form the neutral radical. It is estimated that 85% of (•)OH adducts are oxidizing while 13% are reducing. The yields of the reducing radicals on reaction of e(aq)(-) with 8-oxoA or 8-oxoG amount to ∼43 and 77% of the respective yield of e(aq)(-), whereas the extent of formation of any oxidizing radicals is ≤2%. In summary, radical intermediates from 8-oxoA or 8-oxoG and their redox potentials have been determined so that 8-oxoA and 8-oxoG, if preformed endogenously, may act as primary sinks for oxidized DNA damage if present close to DNA radicals induced radiolytically.